Digital promotional strategies for multi-brand retail fashion stores in India. Issue 2 (17th February 2020) - Upadhyay, Himanshu Kumar; Singh, Pragya; Singh, Nripendra
Abstract: Technology has the ability to heavily influence marketing theory and customer's choice while shopping. This research takes reference from David McClelland's Three Need Theory, (1960) of Power, Affiliation and Achievement, which encourages the marketers to continuously frame their strategies to gain a wider view of the target population and maximize their profits. The big question is: what should be the approach of using the digital promotional tools for different types of retail stores, including both new entrants and existing players, based on their target population from varied income groups? This paper targets to answer these questions.